Review: Methods of firing rate estimation - Tomar, Rimjhim (Biosystems, 2019)
Neuronal firing rate is traditionally defined as the number of spikes per time window. The concept is essential for the rate coding hypothesis, which is still the most commonly investigated scenario in neuronal activity analysis. The estimation of dynamically changing firing rate from neural data can be challenging due to the variability of spike times, even under identical external conditions; hence a wide range of statistical measures have been employed to solve this particular problem. In this paper, we review established firing rate estimation methods, briefly summarize the technical aspects of each approach and discuss their practical applications.
Keywords: Neurons; stochastické procesy; algoritmy; akční potenciály; Algorithms; Models, Neurological; Action Potentials; Bayes Theorem; Probability; pravděpodobnost; Bayesova věta; zvířata; Humans; interpretace statistických dat; Data Interpretation, Statistical; Stochastic Processes; neurony; modely neurologické; lidé; Animals